Analisis Perilaku Sosial Anak Putus Sekolah: Tinjauan Empiris tentang Perilaku Sosial Anak Putus Sekolah di Desa Paleran, Kecamatan Umbulsari, Kabupaten Jember - Fudhlah Ilmiyyah; Evrilia Nikmatus Sholeha; Marchelinda Okta Brianti Eka Putri; Fiona Anggraeni; Haidar Fadhilatiin Isyroq; Nadia Khairun Nisa; Alfi Fahrani; Chita Lintang Fatica; Siti Khumairoh; Lailatul Niasari; Mohammad Rofik; Hafidz Ihza Restu Putra; Moh Hafidz Putra P; Dwi Rizky Firdaus; Khoirunisa Wahida (Universitas 17 Agustus 1945, 2024)
This study aims to determine the social behavior and factors that cause children to drop out of school in the community of Paleran Village, Umbulsari District, Jember Regency. The research conducted is socio-cultural research that uses descriptive qualitative and quantitative research methods by determining the sample through Purposive Sampling technique by selecting several informants who have criteria determined by the researcher, namely knowing about the Social Behavior of School Dropouts. The results showed that the factors that cause children to drop out of school in the community of Paleran Village, Umbulsari District, Jember Regency most children choose to work or continue their education at the Islamic Boarding School. In addition, other factors such as children's interest and motivation to enthusiasm for learning are lacking, early marriage and death and family economic factors also so that the child cannot continue his education.